(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
For countries that are members of the Eurasian Economic Union, the need for special legal solutions for labor with a foreign employer arose during a period of fundamental economic and legal transformations that contributed to the arrival of foreign investment in the USSR. An analysis of the experience of legal regulation of labor among foreign investors in member countries of the Eurasian Economic Union shows that work is required to adapt national labor law systems to new realities. Such work implies a transition to qualitatively different legal solutions, which should provide not only conflict of law, but also special substantive regulation. In some cases, national labor law systems are insufficient. The national level at which cross-border legal regulation in the field of labor is carried out needs to be supplemented by a level that involves transnational legal regulation. Depending on where they arise and where they are implemented, and, therefore, under what regulation labor relations, complicated by a foreign element due to the special status of the employer, fall, it is proposed to divide them into cross-border and transnational.